Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/ejhg.2011.175
|View full text |Cite|
|
Sign up to set email alerts
|

Isolated NIBPL missense mutations that cause Cornelia de Lange syndrome alter MAU2 interaction

Abstract: Cornelia de Lange syndrome (CdLS; or Brachmann-de Lange syndrome) is a dominantly inherited congenital malformation disorder with features that include characteristic facies, cognitive delays, growth retardation and limb anomalies. Mutations in nearly 60% of CdLS patients have been identified in NIPBL, which encodes a regulator of the sister chromatid cohesion complex. NIPBL, also known as delangin, is a homolog of yeast and amphibian Scc2 and C. elegans PQN-85. Although the exact mechanism of NIPBL function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Interestingly, Mau2 1/2 mice were indistinguishable from wild type mice, consistent with the notion that mutations in MAU2 have not been identified in CdLS thus far (Seitan et al, 2006;Braunholz et al, 2012). In contrast, Nipbl 1/2 neonates appeared small ( Fig.…”
Section: Resultssupporting
confidence: 84%
“…Interestingly, Mau2 1/2 mice were indistinguishable from wild type mice, consistent with the notion that mutations in MAU2 have not been identified in CdLS thus far (Seitan et al, 2006;Braunholz et al, 2012). In contrast, Nipbl 1/2 neonates appeared small ( Fig.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, to evaluate the role of NIPBL in our model we introduced two different SNVs previously shown to disrupt binding of NIPBL to the cohesin component MAU2 (G15R, P29Q)(29). Surprisingly, these single alterations abrogated the ability of cells carrying the fusion to serially replate as well as to induce leukemia (Supplementary Figure S15A–B).…”
Section: Resultsmentioning
confidence: 99%
“…Vertebrate Scc2 and Scc4 orthologs interact physically through their amino termini (10,13,17,18), but budding yeast Scc2 appears to lack the corresponding amino-terminal region. Nevertheless, we found that Scc2 cleavage prevents its coimmunoprecipitation with Scc4, indicating that the budding yeast Scc2 amino-terminal domain is required for stable interactions with Scc4.…”
Section: Discussionmentioning
confidence: 99%
“…The amino termini of human and Xenopus Scc2 homologs are required for interactions with their respective Scc4 orthologs (10,13,17,18). Whether this requirement is true in budding yeast is unclear, however, because S. cerevisiae Scc2 lacks the corresponding amino-terminal region present in multicellular eukaryotic homologs.…”
Section: Scc2 Cleavage Eliminates Its Interactions With Scc4 and Redumentioning
confidence: 99%
See 1 more Smart Citation